Empowering Health Cadres in Reproductive Health Education through a Community Midwifery Approach - Samsinar Samsinar; Indrawat Aris Tyarini; Gustini Gustini; A. Wardah Muzfah; Matilda Martha Paseno (Edukasi Ilmiah Indonesia, 2026)
Introduction: Reproductive health remains a significant public health concern, particularly in communities with limited access to accurate information and services. Health cadres play a strategic role in delivering community-based education; however, their capacity in reproductive health education is often inadequate. This program aimed to empower health cadres in reproductive health education through a community midwifery approach. Methods: A community service program was conducted using a participatory approach with a one-group pretest–posttest design. A total of 25 health cadres participated in structured training sessions facilitated by midwives. The intervention included lectures, group discussions, role-playing, and case-based learning covering adolescent reproductive health, family planning, and prevention of sexually transmitted infections. Data were collected using structured questionnaires and analyzed using descriptive statistics and paired t-tests. Results: The findings showed a significant improvement in knowledge scores, increasing from a pretest mean of 55% to a posttest mean of 82%, indicating a 27% increase. In addition, cadres demonstrated improved communication and counseling skills during simulation sessions. The involvement of midwives contributed to a deeper understanding and the practical application of reproductive health education. Conclusion: The community midwifery approach is effective in improving the knowledge and skills of health cadres in reproductive health education. This model has the potential to strengthen community-based health promotion and should be considered for broader implementation.